Development and evaluation of an automatically adjusting coarse-grained force field for a β-O-4 type lignin from atomistic simulations. (17th November 2016) - Li, Wenzhuo; Zhao, Yingying; Huang, Shuaiyu; Zhang, Song; Zhang, Lin
Abstract: This goal of this work was to develop a coarse-grained (CG) model of a β -O-4 type lignin polymer, because of the time consuming process required to achieve equilibrium for its atomistic model. The automatic adjustment method was used to develop the lignin CG model, which enables easy discrimination between chemically-varied polymers. In the process of building the lignin CG model, a sum of n Gaussian functions was obtained by an approximation of the corresponding atomistic potentials derived from a simple Boltzmann inversion of the distributions of the structural parameters. This allowed the establishment of the potential functions of the CG bond stretching and angular bending. To obtain the potential function of the CG dihedral angle, an algorithm similar to a Fourier progression form was employed together with a nonlinear curve-fitting method. The numerical potentials of the nonbonded portion of the lignin CG model were obtained using a potential inversion iterative method derived from the corresponding atomistic nonbonded distributions. The study results showed that the proposed CG model of lignin agreed well with its atomistic model in terms of the distributions of bond lengths, bending angles, dihedral angles and nonbonded distances between the CG beads. The lignin CG model also reproduced the static and dynamic properties of the atomistic model. The results of the comparative evaluation of the two models suggested that the designed lignin CG model was efficient and reliable.